Antimicrobial Activity of Turmeric: A Systematic Review - Mehta, Abhishek; Jain, Arti; Jain, Sourabh (Nepalese Medical Journal, 2022)
Turmeric or Curcuma longa is a popular healing herb in Ayurvedic medicine. Due to its potential health benefits including antimicrobial properties, it is being used in herbal medicines in the treatment of several systemic diseases, especially in the Indian subcontinent. In this review, we have given an up-to-date overview of the anti-infective properties of the Turmeric plant with a special focus on its antibacterial activity. Published articles relevant to the research questions were searched in their database (PubMed, Scopus, Web of Science). Additionally, studies were searched through snowballing. The articles were included as per eligibility for data extraction. The included articles were assessed on quality reporting and results were presented using descriptive analysis. This literature review aimed to illustrate the therapeutic properties of the plant “Curcuma longa”.A total of 32 publications out of 671 articles were selected through online and snowballing literature searches. Out of these 32 articles, 22 were original research articles and 9 were systematic reviews after removing the duplicates and non-eligible studies. Most of the original articles analyzed were from India. In view of rapidly emerging antimicrobial resistance amongst the prevailing pathogens, the present study highlights the need of exploring alternate preventive and treatment strategies that are safe, effective, and economical when compared to existing methods. There is immense scope of such studies focused on the possibilities of mining the antimicrobial potential of bioactive phytochemicals derived from herbal sources like Turmeric.